Associations of coagulation factors IX and XI levels with incident coronary heart disease and ischemic stroke: the REGARDS study. (9th May 2017) - Olson, N. C.; Cushman, M.; Judd, S. E.; Kissela, B. M.; Safford, M. M.; Howard, G.; Zakai, N. A.
Abstract : Essentials Coagulation factors (F) IX and XI have been implicated in cardiovascular disease (CVD) risk. We studied associations of FIX and FXI with incident coronary heart disease (CHD) and stroke. Higher FIX antigen was associated with incident CHD risk in blacks but not whites. Higher levels of FIX antigen may be a CHD risk factor among blacks. Summary: Background: Recent studies have suggested the importance of coagulation factor IX and FXI in cardiovascular disease (CVD) risk. Objectives: To determine whether basal levels of FIX or FXI antigen were associated with the risk of incident coronary heart disease (CHD) or ischemic stroke. Patients/Methods: The REasons for Geographic And Racial Differences in Stroke (REGARDS) study recruited 30 239 participants across the contiguous USA between 2003 and 2007. In a case–cohort study within REGARDS, FIX and FXI antigen were measured in participants with incident CHD ( n = 609), in participants with incident ischemic stroke ( n = 538), and in a cohort random sample ( n = 1038). Hazard ratios (HRs) for CHD and ischemic stroke risk were estimated with Cox models per standard deviation higher FIX or FXI level, adjusted for CVD risk factors. Results: In models adjusting for CHD risk factors, higher FIX levels were associated with incident CHD risk (HR 1.19; 95% confidence interval [CI] 1.01–1.40) and the relationship of higher FXI levels was slightly weaker (HR 1.15; 95% CI 0.97–1.36). When stratified by race, the HR of FIX was higher in blacks (HR 1.39; 95% CI 1.10–1.75) than in whites (HR 1.06; 95% CI 0.86–1.31). After adjustment for stroke risk factors, there was no longer an association of FIX levels with ischemic stroke, whereas the association of FXI levels with ischemic stroke was slightly attenuated. Conclusions: Higher FIX antigen levels were associated with incident CHD in blacks but not in whites. FIX levels may increase CHD risk among blacks.